Evaluation of the Median Sacral Artery in 30 Postmortem Specimens. (1st June 2016) - Colak, T.; Bamac, B.; Ceylan, S.; Kurnaz, S.; Gundogmus, U.N.; Uzun, I.
Abstract: Thirty median sacral arteries (19 males and 11 females) that ranged from 34 to 66 years old (mean age, 50.8 years) postmortem specimens were studied. Sections of formalin-fixed vessels were stained with hematoxylin and eosin. The measurements obtained included tunica media thickness and external diameter of the median sacral artery. The external diameter of the median sacral artery was 1315.06±291.18μm for males and 1389.31±243.06μm for females. The tunica media thickness of the median sacral artery was 210.81±50.43μm for males and 256.35±31.41μm for females. Females have greater external diameter and tunica media thickness. The difference between the tunica media thickness of the median sacral artery for male and female was statistically different (P Â0.05).